2004
DOI: 10.1080/02688690400022763
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients with severe head injury in coma from the outset--has anything changed?

Abstract: Advancing age is known to be a determinant of outcome in head injury. We have sought to discover whether there has been any change in the outcome of elderly patients with severe head injury in Newcastle, where these patients have continued to be treated with maximum intervention. A review of prospectively collected data from the Newcastle Head Injury Database for the period 1990 to 2000 was carried out. All patients aged 70 years and above who had sustained a severe head injury (Glasgow Coma Score of 8 or less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…This was, in contrast to some previous published studies, in which none of the comatose traumatic brain injury patients aged above 70 years achieved good recovery and only 1% achieved independency in activity of daily living. [1415] Kilaru et al . reported that all traumatic brain injury patients aged 65 years or above with admission GCS 3/15 died.…”
Section: Discussionmentioning
confidence: 99%
“…This was, in contrast to some previous published studies, in which none of the comatose traumatic brain injury patients aged above 70 years achieved good recovery and only 1% achieved independency in activity of daily living. [1415] Kilaru et al . reported that all traumatic brain injury patients aged 65 years or above with admission GCS 3/15 died.…”
Section: Discussionmentioning
confidence: 99%
“…Acute subdural hematoma was the commonest pathology for elderly TBI [30], which corresponds with a coroner’s report that subdural hematoma was the commonest lesion of the deceased elderly persons with head injuries [12]. …”
Section: Pathologymentioning
confidence: 74%
“…The outcome was similar in the same center over 10 year’s time. However, the sample size was small [30]. …”
Section: Functional Outcomementioning
confidence: 99%
“…Trauma is a leading cause of death among the elderly 1 . Poor outcomes in elderly patients compared with the young have been previously reported, 2,3 and there have been calls to carefully consider active treatment in the elderly trauma patients with severe head injury 4,5 . Cagetti et al 6 reported a 100% mortality rate in elderly patients aged >80 years, with a Glasgow Coma Scale (GCS) of 11 or less, and other studies have reported that surgery on elderly patients with a GCS of 5 or less was incompatible with survival 7 .…”
Section: Introduction and Aimsmentioning
confidence: 99%